Pruritus as a leading symptom: clinical characteristics and quality of life in German and Ugandan patients - Weisshaar, Elke; Apfelbacher, Christian; Jäger, G.; Zimmermann, E.; Bruckner, Thomas; Diepgen, Thomas L.; Gollnick, Harald (British journal of dermatology, 2006)
Background Pruritus is the most frequent and distressing symptom associated with dermatoses and various internal and neurological diseases.Objectives To investigate two different populations of patients with pruritus, one in Germany and one in Uganda, with a particular focus on clinical characteristics, aetiology and quality of life.Methods We investigated by questionnaire 132 patients (59 men, 73 women, mean age 54·5 years) who were referred to the Department of Dermatology at the University Hospital of Magdeburg, Germany, with the diagnosis of pruritus as a leading symptom. The questionnaire was also applied in 84 patients who consulted the Dermatology Clinic at Mbarara, Uganda for pruritus. The questions referred to personal data and disease history of the individual, history and present occurrence of concomitant diseases, present and past therapy, quality, frequency and triggers of itching and scratching, other disorders and complaints, quality of life and impact on work and disability.Results Seventy‐five (57%) of the German patients had pruritus due to dermatoses, 47 patients (36%) had pruritus due to a systemic disease and in 10 patients (8%) pruritus was of unknown origin. Most had a history of pruritus of several months up to years. Pruritus associated with dermatoses mostly affected the whole body and was permanent with an undulatory character. Affective reactions such as aggression and depression occurred more frequently in dermatological patients compared with those with systemic pruritus. The former group felt that pruritus had a greater impact on their lives. Almost all Ugandan patients had pruritus due to dermatoses except for three patients with pruritus of unknown origin. Eczema and prurigo were the most frequently observed dermatoses in both German and Ugandan patients. Patients with pruritus in both populations showed an impaired quality of life. There was no pronounced difference between the populations with regard to feelings of depression and suicidal thoughts.Conclusions A great deal of helpful information in this complex group of patients can be obtained using this questionnaire. Pruritus has a major impact on quality of life and especially impairs those patients with pruritus associated with dermatoses and pruritus of unknown origin.